Unraveling the principles of auditory cortical processing: can we learn from the visual system? - King, A; Nelken, I (2009)
Studies of auditory cortex are often driven by the assumption, derived from our better understanding of visual cortex, that basic physical properties of sounds are represented there before being used by higher-level areas for determining sound-source identity and location. However, we only have a limited appreciation of what the cortex adds to the extensive subcortical processing of auditory information, which can account for many perceptual abilities. This is partly because of the approaches that have dominated the study of auditory cortical processing to date, and future progress will unquestionably profit from the adoption of methods that have provided valuable insights into the neural basis of visual perception. At the same time, we propose that there are unique operating principles employed by the auditory cortex that relate largely to the simultaneous and sequential processing of previously derived features and that therefore need to be studied and understood in their own right.